Pengaruh Rekrutmen Terhadap Kinerja Karyawan Pada PT. Orix Indonesia Finance Palembang - Yuliza (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2019)
This study aims to analyze the influence of recruitment on employee performance. This study uses populations of 82 respondances where the populations are the employees of PT. Orix Indonesia Finance. This study uses primary data and the method of analyze is simple linear analysis. This result showed that 62,7% of recruitment variables influenced employee performance and there were 37,3% for subsequent researchers to examine other variables affecting performance such as compensation, productivity, leadership and development career.